2022
DOI: 10.1177/00336882221089051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Translanguaging in Online Peer Feedback on Chinese University English-as-a-Foreign-Language Students’ Writing Performance

Abstract: Peer feedback has long been recognized for its value in improving second language learning outcomes. However, limited attention has been given to the potential influence of translanguaging in the process of online peer feedback on learners’ second language writing performance. To fill the gap, we carried out this mixed-methods study to examine to what extent translanguaging in online peer feedback contributes to improvement in second language writing performance. A total of 79 Chinese English-as-a-foreign-lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In the last two stages of the CTSTS, students share their ideas with their classmates and then reflect on feedback from their peers, which is crucial. In both physical and online courses, peer feedback can improve learners’ writing abilities (Harris & Leeming, 2022; Paul Sun & Jun Zhang, 2022; Z. Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the last two stages of the CTSTS, students share their ideas with their classmates and then reflect on feedback from their peers, which is crucial. In both physical and online courses, peer feedback can improve learners’ writing abilities (Harris & Leeming, 2022; Paul Sun & Jun Zhang, 2022; Z. Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that emotional intelligence has a positive impact on academic attainment ( Ran et al, 2021 ). In another study, the relationship between emotional intelligence and English language learning was investigated ( Paul Sun and Jun Zhang, 2022 ). The results showed that the two variables were substantially connected.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have become increasingly interested in the elements that influence English as a foreign language learners’ performance in recent years. According to Paul Sun and Jun Zhang (2022) , when compared to other courses, oral learners have a higher level of anxiety. Anxiety over speaking in public is a typical problem among English language students.…”
Section: Research Literaturementioning
confidence: 99%
See 2 more Smart Citations